Organizational structures and adaptation to changing environmental conditions: Challenges and implications (2017)
Introduction: This article, prepared in 2017 at the Universidad Distrital Francisco José de Caldas, identifies some of the characteristics, advantages, and limitations of organizational structures that seek to increase the ability to adapt to changing environmental conditions. Methodology: a) it is argued that business organizations are information processing systems; b) it is shown that organizational structures can be understood as information circulating networks; c) the research literature published in the 2010-2016 period is reviewed; it was methodically and exhaustively analyzed for trends, advances, methodology, future research, results, and conclusions in the twenty main journals of the Business, Management and Accounting category of Scimago; and d) research challenges and problems not yet overcome are set out. Results: The characteristics, advantages, and limitations of organizational structures other than hierarchical control are identified. Future research projects in the design of organizational structures that increase the ability of the system to adapt to changing environmental conditions are planned. Conclusions: The ability to adapt linked to the processing of high volumes of information is a challenge faced daily by organizations which could be satisfactorily addressed by implementing flexible structures.